Thermal and dielectric properties of some epoxy compositions - Pokorska-Młodzińska, O.; Pokorska, Z.; Spadło, M. (Polimery, 2022)
Thermal properties (glass transition temperature Tg values) of the eight epoxy compositions consisted of various commercial epoxy resins and epoxy-novolaks, cured with novolaks themselves or combined with dicyandiamide in the presence of 2-ethyl-4-methylimidazole as a catalyst (Table 1). Composition 1 was another system cured just with triethylenetetramine, without a catalyst. The compositions tested, except for the last one, showed similar high Tg values (on average 188°C), independent on the composition constitution. Dielectric properties (dielectric constant e and loss factor tg δ) of three compositions were determined. Dependences of these properties on temperature (20-200°C) and frequency (0.01-10 000Hz) were characterized (Table 2-4). It was found that two compositions (No. 6 and 7 in Table 1) fulfill the requirements for electronic and electrical engineering goods, at Tg conditions.